Odpowiedź :
Odpowiedź:
6 i 1/4 - 3 i 5/6 = 6 i 3/12 - 10/12 = 5 i 15/12 - 10/12 = 5 i 5/12
7 i 1/6 + 6 i 1/8 = 7 i 4/24 + 6 i 3/24 = 13 i 7/24
6 i 1/3 - 3 i 5/6 = 6 i 2/6 - 3 i 5/6 = 5 i 8/6 - 3 i 2/6 = 2 i 6/6 = 3
[tex]6 \frac{1}{4} - 3\frac{5}{6} =6 \frac{3}{12} -3 \frac{10}{12} = 5\frac{15}{12} - 3\frac{10}{12} = 2 \frac{5}{12}[/tex]
[tex]7 \frac{1}{6} + 6 \frac{1}{8} =7 \frac{4}{24} + 6 \frac{3}{24} = 1 \frac{1}{24}[/tex]
[tex]6 \frac{1}{3} - 3 \frac{5}{6} = 5 \frac{8}{6} - 3\frac{5}{6} = 2 \frac{3}{6} = 2\frac{1}{2}[/tex]